Evaluation of the Profitability Performance of Regional Development Banks Using Panel Regression: A Study on Four Provinces in Indonesia - Gita Danupranata; Agus Tri Basuki; Gusdinda Ramadhanti Putri (International Publisher (YAPENBI), 2025)
This study aims to analyse the influence of ROE, BOPO, NPL, LDR, NIM, and reserve requirement on profitability as measured by Return on Assets (ROA) in four Regional Development Banks (BPD) in Indonesia, namely BPD DKI Jakarta, BPD Central Java, BPD DIY, and BPD East Java during the period 2017Q1 to 2024Q4. The method used is panel data regression using the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM) approaches. The results of the Chow test showed that FEM was better than CEM, while Hausman's test showed that FEM was also more accurate than REM. Thus, the best model used is the Fixed Effect Model. The results of the analysis showed that the variables ROE, NPL, LDR, NIM, and GWM had a positive and significant effect on ROA, while BOPO had a negative and significant effect. The NIM variable is the most dominant factor in increasing profitability, while BOPO is the main obstacle. These findings confirm the importance of operational efficiency and interest margin management in improving BPD's financial performance. This research provides implications for BPD management to focus more on cost control strategies and interest income optimization to increase profitability in a sustainable manner.